Empowerment of The Sungai Nonam Palm Oil Farmer Groups in Improving Family’s Economy - Saputra Yasa, Rakes; Syafriwaldi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The main problem in this study is the empowerment of Sungai Nonam oil palm farmer group in improving family economy in Nagari Paru, Sijunjung District. This study aims to describe the empowerment of Sungai Nonam Oil Palm Farmer Group in improving family economy. The research method used by the author is descriptive qualitative with data collection techniques through observation, interviews, and documentation. This research is included in field research, namely research conducted in the field by seeing directly and going directly to the field location. Field research was conducted by exploring data sourced from the research location or field from respondents in Nagari Paru Sijunjung. The results of the research conducted by researchers in the field show that training and mentoring can improve the knowledge and skills of Sungai Nona farmer group members in cultivating, caring for, and marketing oil palm, thus having an impact on increasing family income. Organization and mutual cooperation strengthen solidarity, facilitate the distribution of tasks, and build a savings and loan system and economic cooperation between members, which also encourages shared prosperity. Management of family economic activities is carried out through business diversification and collective management of harvest results, so that economic risks can be minimized. Supporting factors in the Sungai Nonam farmer empowerment group include land area, number of family members, income from farming, and support from the government and partner companies.